Considerations about Old Maps in the Digital Era (diségno, 2019)
Old maps often corroborate the studies performed in many fields of design, but they also provide a wealth of precious data which, in an increasingly interdisciplinary manner, can retrace transformations in parts of a territory or urban context; these changes are often radical, made either by man or triggered by natural events.Although maps are sometimes poorly appreciated the interaction between their signs creates and transmits significations that depend on their historical and social context as well as on their interpretation, i.e., the way in which the user intends to use the cartographic drawing, quite apart from the reason why it was produced.This article focuses primarily on nineteenth-century maps; during this century extensive progress was achieved in the fields of science, technique and organisation; this had not only a fallout on map making, but also led to the emergence of several important figures in the fields of education and technique.
Keywords: iconic/symbolic; cartographic culture; transformations